Intravenous Cyclophosphamide and Plasmapheresis in Dialysis-Dependent ANCA-Associated Vasculitis - LITTLE, MARK (My University, 2013)
BACKGROUND AND OBJECTIVES: Induction therapy with oral cyclophosphamide (CYP) has been a mainstay of treatment in patients with severe renal failure secondary to ANCA-associated vasculitis (AAV). Recent evidence proposes using pulsed intravenous CYP in less severe disease to minimize adverse events. It is unclear if this can be translated to those with dialysis-dependent renal insufficiency. DESIGN, SETTING, PARTICIPANTS, & METHODS: All AAV patients presenting between 2005 and 2010 requiring dialysis at presentation were retrospectively analyzed. Patients were treated with plasma exchange, corticosteroids, and intravenous CYP. Rate of dialysis independence at 3 and 12 months and adverse effects were assessed and compared with the outcome of the plasmapheresis, prednisolone, and oral CYP arm of the randomized MEPEX (methylprednisolone versus plasma exchange) trial. RESULTS: Forty-one patients were included. At 3 months, 3 (7.3%) patients had died on dialysis, 12 (29.3%) remained dialysis dependent, and 26 (63.4%) were dialysis independent (creatinine, 2.5 mg/dl; GFR, 26 ml/min per 1.73 m(2)). Four patients subsequently reached ESRD at a median time of 83 days. Thirty-seven (90%) patients reached 1 year follow-up, 13 (35%) remained dialysis dependent, and 24 (65%) had independent renal function. Eleven patients (27%) had episodes of leukopenia (white cell count <4×10(9)/L) during CYP therapy and 17 (41%) experienced infectious complications. This compares favorably with the dialysis-dependent cohort treated with plasmapheresis in the MEPEX study in which 51% were alive with independent renal function at 1 year. CONCLUSIONS: Intravenous CYP used with corticosteroids and plasmapheresis may be an effective alternative to oral CYP in patients with dialysis-dependent AAV.
PUBLISHED
Keywords: Nephrology; Immunology, Inflammation & Infection